Awareness among the Patients of Chronic Suppurative Otitis Media about the Disease and its Complications - Sheikh Ishaq Ahmed Qureshi; Muhammad Arshad Chohan; Hassaan Uddin Hassan; Sana Arshad Chohan (Journal of Bahria University Medical and Dental College)
Objective:To assess the level of awareness among patients of chronic suppurative otitis media (CSOM) about disease and its complications.